Building a case for regional local content policy: The hollowing out of mining regions in Chile. Issue 2 (April 2020) - Atienza, Miguel; Arias-Loyola, Martín; Lufin, Marcelo
Highlights: Local content policies require an analysis of their spatial dimension. Mining is weakly embedded in the Chilean mining regions. Opportunities for linkages development, creation of jobs and knowledge transfer are weak. Spatially blind local content policies reinforce regional inequalities. Regional local content policies can contribute to embed mining in Chilean regions. Abstract: The meaning of 'local' in local content policies tends to be fuzzy, directly affecting their design, impacting their efficiency and influencing their evaluation. In this article, we analyse the spatial dimensions of local content policies at a regional scale in the context of global fragmentation of production in the extractive industries. We do so through a multi-scalar analysis of changes that have taken place in the organization of extractive industries, with special emphasis on how this has reduced the territorial embeddedness of activities in mining regions. We study the evolution of these regions in Chile, an ideal case to explore the consequences of the lack of application of local content policies at a regional scale. Empirical results depict an ongoing process of 'hollowing out' in extractive regions in terms of opportunities for linkages development, creation of thick labour markets and knowledge transfer, and justifying the application of specific local content policies with an explicit and clear regional dimension and long-term perspective.